2008
DOI: 10.1213/ane.0b013e3181602e41
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns in Choice of Left Double-Lumen Tube Size for Thoracic Surgery

Abstract: Under the conditions of this pilot study, the use of smaller than conventionally sized DLT was not associated with any differences in clinical intraoperative outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…[6] Smaller sizes were required in 2% (6/300) of American adult patients because of the greater difficulty of insertion into the left mainstem bronchus than in the glottis. [7] In the current study, difficulty in passage through smaller cricoid cartilages occurred in seven patients (2.5%, 7/280).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…[6] Smaller sizes were required in 2% (6/300) of American adult patients because of the greater difficulty of insertion into the left mainstem bronchus than in the glottis. [7] In the current study, difficulty in passage through smaller cricoid cartilages occurred in seven patients (2.5%, 7/280).…”
Section: Discussionmentioning
confidence: 51%
“…[7] In 8 of 32 short Asian women (height, <152 cm), a left DLT <32-Fr in size (8.7 mm outer diameter of the bronchial lumen, Broncho-Cath™; Mallinckrodt, St. Louis, MO, USA) was needed. [6] Moreover, left DLTs <35-Fr (9.6 mm, Broncho-Cath™) in size were needed in 27 of 48 women with heights of 152–160 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Tube exchangers are available in a wide range of sizes (11,14,19 Fr), and if necessary can easily adapted for either oxygen insufflation or jet ventilation (Cook Critical Care, Bloomington, IN.). Tube exchangers are available in a wide range of sizes (11,14,19 Fr), and if necessary can easily adapted for either oxygen insufflation or jet ventilation (Cook Critical Care, Bloomington, IN.).…”
Section: Cohen Blocker 4 Uniblockermentioning
confidence: 99%
“…A large DLT also gives the best conditions for fiberoptic bronchoscopy and suctioning through the tube. On the other hand, a too-large DLT could cause bronchial rupture [4] and a too-small DLT could be advanced too deeply, obstructing the upper lobe bronchus, although it has been reported that a 35-Fr DLT can be safely used [5].…”
Section: Introductionmentioning
confidence: 99%